Improving business performance At petrolimex chemicals limited company - Nguyễn, Hải Long (2020)
The business of solvents and industrial chemicals is an area that our Party and State always pay attention to, considering this to be a key, key development investment focus. Over the past years, the business of solvents and industrial chemicals has contributed to the country's industrialization and modernization, stabilizing social security, and supporting much other industry's development. The production and business units in solvents and industrial chemicals provide a large portion of raw materials and fuels for social life and, more importantly, supply raw materials. Input materials are indispensable for other industries. Therefore, the business of solvents, industrial chemicals must continuously be renewed and perfected. Through the thesis “Improving business performance at Petrolimex Chemicals Limited Company,” the author gave the following issues: Firstly, it generalizes the theory of improving business performance in the enterprise by analyzing the performance evaluation criteria such as profitability, capital, labor efficiency evaluation criteria, cost